2017
DOI: 10.3748/wjg.v23.i5.842
|View full text |Cite
|
Sign up to set email alerts
|

Levothyroxine therapy and impaired clearance are the strongest contributors to small intestinal bacterial overgrowth: Results of a retrospective cohort study

Abstract: AIMTo identify a set of contributors, and weight and rank them on a pathophysiological basis.METHODSPatients who have undergone a lactulose or glucose hydrogen breath test to rule out small intestinal bacterial overgrowth (SIBO) for various clinical symptoms, including diarrhoea, weight loss, abdominal pain, cramping or bloating, were seen as eligible for inclusion in a retrospective single-centre study. Clinical data such as co-morbidities, medication, laboratory parameters and other possible risk factors hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 30 publications
0
25
0
2
Order By: Relevance
“…Giloteaux et al demonstrated intestinal dysbiosis resulting from a more proinflammatory gut microbiome that may trigger the immune system ( 30 ). Recently, the relationship between the thyroid with gut microbiome and inflammation became apparent from the associations of both hypothyroidism and levothyroxine use with small intestinal bacterial overgrowth ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Giloteaux et al demonstrated intestinal dysbiosis resulting from a more proinflammatory gut microbiome that may trigger the immune system ( 30 ). Recently, the relationship between the thyroid with gut microbiome and inflammation became apparent from the associations of both hypothyroidism and levothyroxine use with small intestinal bacterial overgrowth ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most participants were women, limiting extrapolation of our findings to both sexes. As we followed the Dutch guidelines for DCT management [17,22], we could not include a control group of prolonged untreated hypothyroidism. However, plasma BCAA and alanine levels during hypothyroidism were compared with a large euthyroid reference group from the same region of The Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased GIT vermicular movement is one of the factors in the development of SIBO. The study involving 1809 people demonstrated that the most important factors in the development of SIBO were immunosuppression, conditions after gastric/intestinal resection and HT [13]. Lauritano E.C.…”
Section: G M I N F L U E N C E O N T H Y R O I D F U N C T I O N F E a T U R E S O F G M C O M P O S I T I O N I N A I D S O F T H E T Hmentioning
confidence: 99%